Non-Uniform Pricing, Output and Welfare under Monopoly - Katz, Michael L. (Review of Economic Studies, 1983)
A monopolist may earn greater profits by setting a nonuniform price schedule (one in which the price varies with the quantity purchased) than by charging a uniform price. In general, the profit maximizing non-uniform price schedule and the welfare maximizing schedule do not coincide. Thus, there may be scope for improving market performance through regulation. The paper considers a regulator who has limited information and authority. The issues addressed centre around the question of whether the level of total market output can be taken as a measure of market performance. Conditions under which welfare is a monotonic function of the level of total output are derived. 1.